2022
DOI: 10.4028/p-ha82nm
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Train Roof-Top Wind Energy Conversion System

Abstract: Cities all around the globe are ramping up efforts to transform their infrastructure in order to achieve a carbon-neutral and sustainable future, resulting in fast electrification of transportation networks. The need for power in this industry is rising, notably in light rail transit. Application of train rooftops wind energy conversion has the potential to power light rail transits with renewable energy. This research paper presents a way to generate electrical energy by utilizing strong wind pressure from li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 64 publications
(70 reference statements)
0
1
0
Order By: Relevance
“…The wind turbine experimental setup was fabricated based on numerical results and experiments were conducted. The results revealed that a single high-torque, low-speed turbine could generate 4-21 W. The research in [18] presented a way to generate electrical energy by utilizing a strong wind pressure from light rail trains that channeled the induced wind toward the turbine. The main aim was to establish a method and system for producing energy utilizing winds that could be conveniently available in the operation of trains.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The wind turbine experimental setup was fabricated based on numerical results and experiments were conducted. The results revealed that a single high-torque, low-speed turbine could generate 4-21 W. The research in [18] presented a way to generate electrical energy by utilizing a strong wind pressure from light rail trains that channeled the induced wind toward the turbine. The main aim was to establish a method and system for producing energy utilizing winds that could be conveniently available in the operation of trains.…”
Section: Literature Reviewmentioning
confidence: 99%